The Risk Management of COVID-19 Pandemic on the Delivery of Goods at PT. Sicepat Ekspress Indonesia - Azhar Aliady, Rozan; ., Indriyati; Kuntohadi, Hendro; Yoel Vebra, Rudolfo; Budiman, Cecep; Purwoko, Harry (KnE Social Sciences, 2023)
This study aimed to identify risks to PT Sicepat Ekspress Indonesia during the COVID-19 pandemic. This study used quantitative and qualitative risk management methods. Data were taken from respondents using a questionnaire and distributed to respondents who were employees of PT Sicepat Ekspress Indonesia and service users of PT Sicepat Ekspress Indonesia during the COVID-19 pandemic. The steps in this research were to identify risk using a risk matrix, measure the threat obtained from respondents with 14 indicators, make a risk map in risk quadrants and determine the risk mitigation steps that the company can take. The result of the study proved that there is a quadrant I risk on the indicator, which is Work from Home (WFH) that reduced employee productivity (3,1.3,1), there are obstacles in supervision and communication of employees who do WFH (3,3.3), and Restrictions on Community Activities (PPKM) can hinder the delivery of goods (3,2.3,2). Keywords: Risk Management, Delivery, Mitigation